Interferência e manejo químico de plantas daninhas na mandioca - Carvalho, Alysson Oliveira de (2021)
In cassava culture, weed competition reduces its productivity making it necessary to adopt control methods. Therefore, the aim was to determine the periods of weed interference in the crop in different modern/improved and traditional varieties; evaluate the selectivity and efficiency of using herbicide in isolation, mixing or sequential application for the control of weeds in the 'IPR B36' variety; in addition to evaluating the selectivity and efficiency of tank mixes and sequential applications of herbicides for the control of weeds in the cultivar 'Paraguay' in conventional and no-tillage systems. Thus, three experiments were carried out. In the first experiment randomized blocks with subdivided plots and four replications were adopted, in which, the plot represented the coexistence with weeds and the subplot the period they coexisted. The growing period of coexistence and weed control with the crop was evaluated, being 30, 60, 90, 120, 150 and 180 days after planting, in addition to a subplot totally free of weeds (control without coexistence) and another subplot maintained in coexistence with weeds (control with coexistence). In the second experiment, the design was randomized blocks with four replications, with the control treatments, clomazone 1.25 kg ha-1, S-metolachlor 1.92 kg ha-1, flumioxazin 0.120 kg ha-1, S-metolachlor + clomazone [1.92 + 1.25 kg ha-1], flumioxazin + clomazone [0.120 + 1.25 kg ha-1], S-metolachlor + flumioxazin [1.92 + 0.120 kg ha-1], S- metolachlor / clomazone 1.92 / 0.120 kg ha-1 and flumioxazin / clomazone 0.120 / 1.25 kg ha-1. In the third experiment, a randomized block design with subdivided plots and four replications was adopted. In which, each plot corresponds to the conventional and no-tillage system and the sub-plot corresponds to the treatments, weed control, weedless control, ametrine + clomazone [1.25 + 1.25 kg ha-1], flumioxazin + S-metolachlor [0, 12 + 1.92 kg ha-1], flumioxazin + clomazone [0.12 + 1.25 kg ha-1], S-metolachlor + clomazone [0.60 + 1.25 kg ha-1], sulfentrazone + S -metolachlor [0.60 + 1.92 kg ha-1], flumioxazin + clomazone / S-metolachlor [120 + 1.25] / 1.92 kg ha-1, sulfentrazone + clomazone / S-metolachlor [0.60 +1.25] / 1.92 kg ha-1, ametrine + clomazone / S-metolachlor [1.25 + 1.25] / 1.92 kg ha-1, flumioxazin + S-metolachlor / clomazone [120 + 1 , 92] / 1.25 kg ha-1, sulfentrazone + S-metolachlor / clomazone [0.60 + 1.92] / 1.25 kg ha-1 and ametrine + clomazone / clomazone [1.25 + 1.25 ] / 1.25 kg ha-1. It was concluded that it was not possible to define the critical weed interference prevention period (CPWC) for the crop, as there was no interaction between the varieties analyzed and the periods of interaction. However, weed competition throughout the crop cycle reduced root productivity by 15%, highlighting the need to adopt weed management measures. The use of herbicide in isolation, mixture, or sequential application in the variety 'IPR B36', was selective for the culture in the evaluated variety, and still shown control until 51 days after planting (greater than 80%). The application of pre-emergent herbicides in mixture or sequential in conventional and no-tillage systems, was selective for the cassava culture variety 'Paraguay' in both systems, with satisfactory yield (greater than 80%) until 112 days after the planting. The use of herbicides with isolated, mixed, or sequential application, was selective for the variety ‘IPR B36’, suggesting that the application of clomazone alone is not recommended. The application of pre-emergent herbicides in no-tillage and conventional systems showed no statistical difference in their productivity, so it is recommended to apply the product with less commercial value by rotating modes of action.